Answer:
[tex]\displaystyle\frac{x^{-a}}{x^{-b}} = x^{b-a}[/tex]
Step-by-step explanation:
We have to write the rule to simplify fractions with negative exponents in the denominator and numerator.
If we have positive exponents, the simplification takes place as following:
[tex]\displaystyle\frac{x^a}{x^b} = x^{a-b}[/tex]
The powers of the same base of numerator and denominator are subtracted.
In case of negative exponents, the simplification takes place in the following manner:
[tex]\displaystyle\frac{x^{-a}}{x^{-b}} = x^{-a-(-b)} = x^{-a+b} = x^{b-a}[/tex]
The powers of the same base of denominator and numerator are subtracted.